Can Bernanke save QE? Bond supply shocks in a DSGE model with a Bernanke, Gertler, and Gilchrist style financial accelerator mechanism - Nelson, G (2016)
This thesis inserts a household preference over bond maturities into a costly state verification financial accelerator model based on Christiano, Motto, and Rostagno’s 2014 AER paper . It is thus building both on the branch of the financial frictions literature that originated with Bernanke, Gertler, and Gilchrist’s 1999 paper, and more recent post-crisis attempts to study the macroeconomic affects of quantitative easing programs within the DSGE framework. It uses a sufficiently large ‘risk shock’ a la Christiano et al. (2014) to introduce a crisis. And then introduces a lagged shock to the outstanding quantity of long term bonds and lagged monetary policy shocks calibrated to match the first round of the Federal Reserve’s Large Scale Asset Purchases (LSAPs) and accompanying constraints on the short rate. The results of this simulation show that in the model QE first reduces investment, which then later amplifies the post-crisis stock market boom.